Cyromazine - an effective insecticide against the american serpentine leafminer (Liriomyza trifolii) infesting tomato (Lycopersicon esculentum) - PATEL, J J; PATEL, N C; JYANI, D B; PATEL, J R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1994-95 and 1995-96 to evaluate the effectiveness of cyromazine in comparison to other synthetic insecticides against american serpentine leafminer, Liriamyza trifolii (Burgess). Cyromazine @ 225 g ai/ha was most effective. Endosulfan @ 140 g ai/ha and dimethoate @ 120 g ai/ha were found equally effective as 2 lower dose of cyromazine (150 and 75 g ai/ha). Endosulfan effectively controlled the tomato fruit borer, Helicoverpa armigera and recorded higher marketable yield.